2007
DOI: 10.1021/bc700154u
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of Glycosylated Arginine–Glycine–Aspartate (RGD) Derivatives for Integrin Targeting

Abstract: Arginine-glycine-aspartate (RGD) derivatives were prepared by a combination of solid-phase and solution-phase synthesis for selective targeting of alpha vbeta 3 integrin expressed in tumors. In order to evaluate the value of a triazole moiety as a proposed amide isostere, the side chain glycosylated cyclic RGD ( cRGD) peptides were synthesized with either a natural amide linkage or a triazole. Affinity of the cRGD constructs for the alpha vbeta 3 integrin was determined in a solid-phase competitive binding ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 28 publications
0
38
0
Order By: Relevance
“…To a solution of glycoside 27 (106 mg, 0.12 mmol) and Fmocprotected L-propargylglycine (41 mg, 0.12 mmol) 22 in tertbutanol (2 mL) and water (4 ml) was added a solution of CuSO 4 (0.04 M, 0.6 mL, 0.024 mmol) and sodium ascorbate (0.08 M, 0.6 mL) in H 2 O. The mixture was stirred overnight, water (6 mL) was added, and the product was extracted with CH 2 Cl 2 (2 × 25 mL).…”
Section: Experimental Section General Experimentalmentioning
confidence: 99%
“…To a solution of glycoside 27 (106 mg, 0.12 mmol) and Fmocprotected L-propargylglycine (41 mg, 0.12 mmol) 22 in tertbutanol (2 mL) and water (4 ml) was added a solution of CuSO 4 (0.04 M, 0.6 mL, 0.024 mmol) and sodium ascorbate (0.08 M, 0.6 mL) in H 2 O. The mixture was stirred overnight, water (6 mL) was added, and the product was extracted with CH 2 Cl 2 (2 × 25 mL).…”
Section: Experimental Section General Experimentalmentioning
confidence: 99%
“…The 1,2,3-triazole group is stable to acid and basic hydrolysis, as well as reductive and oxidative conditions due to its aromaticity. Furthermore, this triazole group is biologically stable [10] and possesses a polarity and size similar to that of an amide bond [11], thereby improving water solubility [12] and allowing the synthesis of a wide-range of compounds with biological potential [13]. Because of these features of the click reaction and the readily accessible building blocks with azide and alkyne, click labeling has become a valuable and powerful tool in PET chemistry [9].…”
Section: Introductionmentioning
confidence: 99%
“…After establishing syntheses of neoglycosides by CuAAC, Rutjes et al [98] reported the synthesis of glycosylated cyclic arginine-glycine-aspartate (RGD) derivatives with either a natural amide bond or a triazole linker for selective targeting of a v b 3 integrin. Solid-phase binding assays revealed no significant difference in binding affinity and biodistribution studies suggested improved pharmacological properties of the triazole-linked compounds [98]. In a subsequent account, Rutjes et al [99] synthesized several new triazole-linked glycosides from protected and unprotected glycosyl donors with propargylglycine and azidoalanine derivatives.…”
Section: Neoglycoside and Neoglycopeptide Synthesis Via Cuaacmentioning
confidence: 99%